Manifesto for an ECNP neuromodulation Thematic Working Group (TWG): non-invasive brain stimulation as a new super-subspecialty - Pallanti, Stefano; Marras, Anna; Dickson, Suzanne L; Adan, Roger AH; Vieta, Eduard; Dell Osso, Bernardo; Arango, Celso; Fusar-Poli, Paolo; Soriano-Mas, Carles; Carmi, Lior; Meyer-Lindenberg, Andreas; Zohar, Joseph (European neuropsychopharmacology, 2021)
Non-Invasive Brain Stimulation (NIBS) techniques and in particular, repetitive Transcranial Magnetic Stimulation (rTMS), are developing beyond mere clinical application. Although originally purposed for the treatment of resistant neuropsychiatric disorders, NIBS is also contributing to a deeper understanding of psychiatric disorders. rTMS is also changing the model of the disorder itself, from “mental” to one of neural connectivity. TMS allows the assessment of brain circuit excitability and eventually, of plastic changes affecting these circuits. While a clinical translational approach is, at the present time, the most adequate to meet the dimensional-circuit base model of the disorder, it refines the standard categorical classification of psychiatric disorders. The discovery of the fundamental importance of the balance between neuroplasticity and inflammation is also now explored through neuro-modulation findings consistently with the evidence of anti-inflammatory actions of the magnetic pulses. rTMS may activate, inhibit, or otherwise interfere with the activity of neuronal cortical networks, depending on stimulus frequency and intensity of brain-induced electric field. Of particular interest, yet still unclear, is how the relatively unspecific nature of TMS stimulation may lead to specific neuronal reorganization, as well as a definition of the TMS-triggered reorganization of functional brain modules, raising attention on the importance of the active participation of the patient to the treatment.. Configuration and state of consciousness of the subject have made subjective experience under treatment regain importance in the neuro-scientific Psychiatry based on the requirement of United States National Institute of Health (NIH) and the substantial importance of the consciousness state in the efficacy of the TMS treatment. By focusing on the subjective experience, a renaissance of the phenomenology offers Psychiatry an opportunity to become proficient and to distinguish itself from other disciplines. For all these reasons, TMS should be included in the cluster of the sub-specialties as a new “Super-Specialty” and an appropriate training course has to be inaugurated. Psychiatrists are nowadays multi-specialists, moving from a specialty to another, vs super-specialist. The cultivation of a properly trained cohort of TMS psychiatrists will better meet the challenges of treatment-resistant psychiatric conditions (disorders of connectivity), through appropriate and ethical practice, meanwhile facilitating an informed development and integration of additional emerging neuro-modulation techniques. The aim of this consensus paper is to underline the interdisciplinary nature of NIBS, that also encompasses the subjective experience and to point out the necessity of a neuroscience-applied approach to NIBS in the context of the European College of Neuro-psychopharmacology (ECNP).
Gesehen am 11.11.2021